2015
DOI: 10.1021/acs.jnatprod.5b00115
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Derived Compatible Solutes Ectoine and 5α-Hydroxyectoine Act as Intestinal Barrier Stabilizers to Ameliorate Experimental Inflammatory Bowel Disease

Abstract: Earlier studies showed that the compatible solute ectoine (1) given prophylactically before induction of colitis by 2,4,6-trinitrobenzenesulfonic acid (TNBS) in rats prevented histological changes induced in the colon and the associated rise in inflammatory mediators. This study was therefore conducted to investigate whether ectoine (1) and its 5α-hydroxy derivative (2) would also be effective in treating an already established condition. Two days after inducing colitis in rats by instilling TNBS/alcohol in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…To our knowledge, this is the first study describing weight loss in ectoine-treated mice. Previous studies have reported either no effect of ectoine on body weight or weight loss in experimental colitis, counteracted by ectoine treatment [ 21 , 44 ]. The mechanism by which ectoine might exert this effect remains unknown and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study describing weight loss in ectoine-treated mice. Previous studies have reported either no effect of ectoine on body weight or weight loss in experimental colitis, counteracted by ectoine treatment [ 21 , 44 ]. The mechanism by which ectoine might exert this effect remains unknown and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…While ectoine lowers the melting temperature of double-stranded DNA, hydroxyectoine conversely elevates it (Seip et al 2011 ). Recently, the field of application is expanding due to studies demonstrating anti-inflammatory effects of ectoine and ectoine derivatives in intestinal bowel disease and carbon nanoparticle induced airway inflammation, as well as protein stabilizing effects in neurodegenerative diseases (Abdel-Aziz et al 2013 , 2015 ; Bazazzadegan et al 2017 ; Unfried et al 2014 ). Promising applications as adjuvant treatment in these diseases led to a gain in CAGR (calculated annual growth rate) for the ectoine market and therefore to a demand for feasible biotechnological production processes (Becker and Wittmann 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a substantial subgroup of ectoine producers (Prabhu et al, 2004;Garcia-Estepa et al, 2006;Bursy et al, 2007;Czech et al, 2018a), ectoine is modified in a position-and stereo-specific reaction by the ectoine hydroxylase (EctD; EC 1.14.11.55) (Inbar et al, 1993;Bursy et al, 2007;Höppner et al, 2014). The resulting 5-hydroxyectoine often possesses superior functionpreserving attributes when compared with ectoine or it is preferentially produced during stationary phase (Borges et al, 2002;Manzanera et al, 2004;Schiraldi et al, 2006;Bursy et al, 2007;Harishchandra et al, 2010;Tanne et al, 2014;Abdel-Aziz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%